Highly Compact Swing Assistive Knee Prosthesis Integrating Active and Passive Hydraulic Systems - Marco Puliti; Federico Tessari; Renato Galluzzi; Nicola Amati; Andrea Tonoli; Matteo Laffranchi (IEEE Access)
This work proposes a novel partially powered knee prosthesis to give full support to swing related activities. It represents a technological step forward when compared to microprocessor-controlled knees. The device is based on the electro-hydrostatic actuation principle, combined with the use of a series rotary valve to aid during dissipative phases. Another key feature is the backdrivability enabled by a directly coupled fluid-based actuation principle. To this end, we present a compact design that is subsequently built and tested experimentally with an able-body adapter to simulate a real-case scenario of level walking and stair tasks. Results are compared with the features of existing commercial and research devices. To the best of the authors’ knowledge, the proposed prosthesis is the most compact electro-hydrostatic swing assistive device with the potential to improve the walking gait, for instance by increasing toe clearance and likely reducing the occurrence of stumbling or falling events. Additionally, the prototype enables stair ascent in a step-over fashion, a capability generally unattainable with commercial microprocessor-controlled knees.